Premature failures in plate bonded strengthened RC beams with an emphasis on premature shear: a review - Jumaat, Mohd Zamin; Rahman, M.A.; Alam, M.A.; Rahman, M.M. (International Journal of Physical Sciences, 2011)
The aim of the present study is to review the performance of plate bonded flexurally strengthened reinforced concrete beams. This paper also describes the methods and materials used for flexural and shear strengthening of reinforced concrete beams and weaknesses of plate bonded systems. The plate bonding method often has some serious premature debonding failure which can be classified as plate end debonding (end peeling), tension delamination and premature shear failure due to insufficient shear reinforcement. Premature failures must be prevented in order to utilize the full flexural capacity of flexural strengthened reinforced concrete beams. Premature shear failure is one of the major concerns of the flexurally strengthened reinforced concrete (RC) beams. Hence, proper design of external shear strengthening system is required for eliminating premature shear failure of flexurally strengthened RC beams. The review focuses on the possible model and design guideline available in the literature for eliminating premature failures. The paper also discusses a probable approach to eliminate premature shear.